Identification of alcohol content in medicines at the pharmacy through observation on secondary packaging - Abdul Rahem (Journal of halal product and research (JPHR), 2018)
Demand of halal medicine in the world is an interesting issue to be discussed, considering that there are still many medicines that are intended to contain impermissible  (haram) ingredients. The halal medicine depends on the active ingredients and additives of medicine, including the production process and storage of medicine. Alcoholic medicine are a polemic in the community, especially about halal medicine. This study aims to identify the alcohol content of syrup preparations in Yakersuda Pharmacy of Bangkalan. An observational study was conducted to observe alcohol content on secondary medicine packaging. The results showed that there were 8 (eight) items of medicine which listed the alcohol content in the secondary packaging, namely: Actifed Plus Dry Cough + Colds with alcohol content (9.9%); Actifed Plus Expektoran (6.93%); Benacol DTM (4%); Benacol Syr (4%); OBH Combi Syr Phlegm (2%); Vicks formula 44 (10%); and Woods Exp Syr (6%). The conclusion is alcohol content in medicine at the Yakersuda Pharmacy more then 1%. Medicines that do not include the composition of alcohol cannot be sure the drug is alcohol free.